ANALISIS KINERJA GURU (Studi Korelasional Antara Kompetensi Dengan Kinerja Guru) Suku Dinas Pendidikan Dasar Kota Administrasi Jakarta Timur - Dharmawati, D.M. (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2017)
Teachers have a very strategic role in efforts to achieve national development goals, particularly in the fields of education, so it is necessary to develop a professional force that is dignified and professional. Teaching profession has the task of serving the community in the field of education. This profession demands provide optimal service to the community in the field of education. In particular, teachers in demand to provide professional services to the learners so that learning objectives are achieved. So the teacher said professional is a person who has the ability and expertise in the field of teacher training so that he is able to carry out its duties and functions as a teacher with a maximum capability. Given that teachers need competence standards that we have professional teachers who meet the standards in accordance with dist. The study aims to determine the correlation between the professional competence of the teacher performance competency SDN / S on the basis of tribal education office in East Jakarta city administration. Performance Analysis of the results of the survey with a sample of 50 teacher respondents, the results obtained, Pedagogic Competence Variables (X1); Professional Competence (X2), and Teacher Performance (Y). Descriptive results Pedagogic Competence (X1) with an average (mean) of 52.54 and standard deviation (standard deviation) of 3.743, with the category being. Professional Competence Variables (X2) with an average (mean) of 36.34 and standard deviation (standard deviation) of 9.343, with a very high category, in the sense of increasing the level of competence of teachers in the profession is very high. Teacher performance variable (Y) with an average (mean) of 66.78 and standard deviation (standard deviation) of 4.995 , with a medium category. Results Correlations obtained value for X1 with Y of 0.815 means that there is a fairly strong relationship between the Pedagogic Competence Teacher Performance . Professional competence X2 with Y teacher performance by 0.430 means there is a significant correlation with performance on Teacher Professional Competence between variables X1 , X2 , and Y.